2017
DOI: 10.1002/nau.23231
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term complications associated with the use of transvaginal mesh in pelvic floor reconstructive surgery: Results from a multi‐institutional prospectively maintained dataset

Abstract: The use of vaginal mesh for pelvic organ prolapse repair appears to result in a higher rate of perioperative complications than native tissue repair. Patients undergoing these procedures should be counselled preoperatively concerning these risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…On the other hand, Hartmann et al have pointed out that short‐term complications (up to 1 year) after TVM surgery are 5%–11%, and long‐term complications are 5%–20% 2 . Mirzazadeh et al have also reported that patients undergoing mesh repair were more likely to experience at least one complication than those who undertook native tissue repair (9.28% vs. 6.15%, p < 0.001), with the overall complication rate also being higher in the mesh group (11.37% vs. 9.39%, p = 0.03) 10 . TVM surgery was introduced in Japan in 2005, and it employed a self‐cut mesh and custom‐made curved needle, instead of kit products, because mesh kits for TVM were not available.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, Hartmann et al have pointed out that short‐term complications (up to 1 year) after TVM surgery are 5%–11%, and long‐term complications are 5%–20% 2 . Mirzazadeh et al have also reported that patients undergoing mesh repair were more likely to experience at least one complication than those who undertook native tissue repair (9.28% vs. 6.15%, p < 0.001), with the overall complication rate also being higher in the mesh group (11.37% vs. 9.39%, p = 0.03) 10 . TVM surgery was introduced in Japan in 2005, and it employed a self‐cut mesh and custom‐made curved needle, instead of kit products, because mesh kits for TVM were not available.…”
Section: Discussionmentioning
confidence: 97%
“…Various TVM complications have been reported, including intraoperative bleeding, bladder injury, ureteral obstruction, infection, dyspareunia and mesh exposure 6,9 . The complication rate of POP surgery is reportedly significantly higher with TVM than with native tissue repair (11.37% vs 9.39%) 25 . Furthermore, TVM is associated with serious complications that might require reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…6,9 The complication rate of POP surgery is reportedly significantly higher with TVM than with native tissue repair (11.37% vs 9.39%). 25 Furthermore, TVM is associated with serious complications that might require reoperation. Therefore, appropriate patient selection and adequate informed consent of the risks are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…NPWT for the pelvic cavity carries a risk of abdominal organ injury. Therefore, it is important to provide sufficient separation from internal organs to perform safe NPWT [ 13 ].According to past reports, pelvic floor reconstruction using skin flap and mesh implantation is effective for separating the abdominal and pelvic cavities [ [14] , [15] , [16] , [17] , [18] ]. In our method, these reconstruction techniques are unnecessary due to the suturing of the levator ani muscle.…”
Section: Discussionmentioning
confidence: 99%